Make It What Way? The Impact of Multiple Standards Regimes - Berman, Danielle (The International Journal of Sociology of Agriculture and Food, 2013)
Agri-food standards are often envisaged as a regulatory tool to create uniformity in production. However, as Dunn argues, ‘standards… produce unique regulatory landscapes rather than the uniform ones standardizers envisage’. To account for this variation, scholars consider contextual factors such as market institutions, cultural norms, and the structural organization of agriculture. I argue that as standards increasingly overlap, intersect, and even contradict eachother, they emerge as significant contextual features in their own right. This article analyses how producers for Russia’s burgeoning fast-food industry respond to the competing demands of multiple agri-food standards. Drawing on interviewsand site visits with Russian agricultural producers and food processors, I illustrate how the presence of multiple competing standards can both undermine expected standardizing effects and empower producers to adopt and incorporate standards in novel ways. I find that in their efforts to satisfy both multinational firms and domestic consumers, producers legitimize practices that may only comply partially with the various standards they claim to meet.